Analisis Yuridis Legalitas Perjanjian Perkawinan Pisah Harta sebagai Perlindungan Hukum bagi Pasangan Suami dan Istri dalam Proses Perceraian - Gabe Putra Lumban Batu; Roida Nababan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Marriage is a basic human need that involves an official agreement between husband and wife, regulating rights and obligations, including the ownership and management of joint property. Under Indonesian law, property acquired during marriage is considered joint property, which often becomes a source of conflict during divorce. To prevent this, Indonesian law recognizes the existence of a marital separation of property agreement, which regulates the separation of assets between spouses from the beginning, whether before or during marriage. A separation of property agreement provides legal protection for personal assets, protects one party from being liable for the partner’s debts, and reduces the potential for disputes during divorce. Therefore, it is important for the public to receive socialization and legal education about the separation of property agreement in marriage to increase understanding of its benefits and protect the rights of married couples in both marriage and divorce. Legal education on this matter can help reduce disputes over joint property and offer better protection for couples who wish to clearly and legally manage their assets.